Determinants of Quality Institutions: A Comparative Analysis of Various Perspectives - Tijani, Hakeem Olatunji (African Journal of Stability and Development (AJSD), 2018)
While institutions are products of human designs, yet, these vital organs differ from one society to another. Responsible for the differences are: geographical location, colonial origin, legal system tradition, ethnolinguistic fragmentation, natural resources endowment, income distribution, international openness and education. How rich these factors are will determine the quality of a country’s institutions. Thus, there is a link between a country’s level of development and the quality of the institutions it operates. This paper examines the relationship between institutions, development and good governance. It argues that economic stagnancy in sub-Sahara Africa can be traced to the poor institutions in these regions.